2019
DOI: 10.3390/ijms20143556
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Molecular Mechanism Underlying Lippia citriodora(Lim.)-Induced Relaxation and Anti-Depression

Abstract: Lippia citriodora ethanolic extract (VEE) and verbascoside (Vs), a phenypropanoid glycoside, have been demonstrated to exert relaxant and anxiolytic properties. However, the molecular mechanisms behind their effects are still unclear. In this work, we studied the effects and action mechanisms of VEE and Vs in vivo and in vitro, on human neurotypic SH-SY5Y cells.TST was conducted on mice treated orally with VEE (25, 50 and 100 mg/Kg), Vs (2.5 and 5 mg/Kg), Bupropion (20 mg/Kg) and Milli-Q water. Higher dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
0
14
0
1
Order By: Relevance
“…Verbenalin, one of the major constituents of this plant, has been reported to exhibit sleep-promoting and antioxidant activities [20,22,23]. In our previous study, we have reported relaxation and anti-depressant effects of lemon verbena (Lippia citriodora) extract, rich in verbascoside and verbenalin, both in the in vitro and in vivo models [24]. In the present study, we have treated hAECs with verbenalin for seven days and conducted microarray analysis to investigate the changes in gene expression and to explore its therapeutic potential for AD.…”
Section: Introductionmentioning
confidence: 97%
“…Verbenalin, one of the major constituents of this plant, has been reported to exhibit sleep-promoting and antioxidant activities [20,22,23]. In our previous study, we have reported relaxation and anti-depressant effects of lemon verbena (Lippia citriodora) extract, rich in verbascoside and verbenalin, both in the in vitro and in vivo models [24]. In the present study, we have treated hAECs with verbenalin for seven days and conducted microarray analysis to investigate the changes in gene expression and to explore its therapeutic potential for AD.…”
Section: Introductionmentioning
confidence: 97%
“…Sabti et al reported that antidepressants targeting the expression of serotonin and noradrenaline only present limitations and that accordingly antidepressant drugs targeting the dopaminergic system have been developed, whereas the antidepressants acting on serotonergic mechanisms lead to enhancement of BDNF levels in rodents ( Sabti et al, 2019 ). Hence, we assessed the mature BDNF levels, noradrenaline and dopamine levels in mice hypothalamus and serotonin level in mice cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Verbascoside, a phenypropanoid glycoside, has been demonstrated to exert antidepressant and anxiolytic effects through modulation of cAMP, calcium homeostasis (calcium channels), and energy metabolism [ 35 – 37 ]. Our behavior test results indicted verbascoside at 60 mg/kg displayed anxiolytic and antidepressant activity (Additional file 1 : Figure S4).…”
Section: Discussionmentioning
confidence: 99%